Teaching Competencies in Nursing Professors: Visions of Students and Academics - Quintana Alonso, Raúl; García Redondo, Eva; Ortega, María Miana; Chamorro Rebollo, Elena; Cieza García, José Antonio (Investigación y Educación en Enfermería, 2024)
Objective. This work sought to know the view of Nursing professors and students about the competencies the faculty staff must have to deploy their educational function with maximum quality and efficiency. Methods. Descriptive qualitative study through focus groups conducted with professors, students and recent Nursing career graduates from universities in Spain. Results. The importance of the proposed teaching competencies was delved into, highlighting the importance of professors knowing the context in which they teach, having the ability to self-evaluate their activity, and having adequate interpersonal communication skills, and deploy the teaching-learning process by performing proper planning, using new technologies, and knowing how to engage in teamwork. Moreover, a small discrepancy was detected in relation to disciplinary competence, which students felt was of importance, but which academics indicated is taken for granted in nursing professors; competencies directly related to the act of teaching must be enhanced. Conclusion. Practical unanimity was found between academics and students in affirming that the competencies investigated are important for adequate development of the teaching activity in nursing professors. In all cases, the urgent need was highlighted for nursing professors to have adequate teaching training to provide their students with formation of the highest quality.